County lines : exploitation and drug dealing amongst urban street gangs - Harding, Simon (Criminologist) (Bristol University Press, 2020)
Drawing upon extensive research amongst gang members, dealers and drug users, this timely book provides a comprehensive insight into the 'County Lines' phenomenon. Shedding new light on this urgent topic on government agendas, this is an invaluable contribution to the literature on gangs, youth violence and organised crime.